شرح الحديث بالقران الكريم عند الحافظ ابن حجر العسقلاني - Shumsudin Yabi; Mesbahul Hoque; A. Irwan Santeri Doll Kawaid; Muhammad Yosef Niteh; Fadlan bin Mohd Othman; Akila Mamat (Penerbit USIM, 2024)
PAPER PROCEEDINGS: THE 9TH INTERNATIONAL CONFERENCE ON QURAN AS FOUNDATION OF CIVILIZATION SWAT 2023: “AL QURAN AS A SOURCE OF REVELATION IN BUILDING A CIVILIZED SOCIETY”/ Edited by : Dr. Nadiah Ramlan, Dr. Irwan Santeri Doll Kawaid, Dr. Kauthar Abd Kadir, Nurfatin Nazilah Zainol